Technical support essentials : advice you can use to succeed in technical support - Sanchez, Andres R. (Apress, 2009)
"Technical Support Essentials is a book about the many facets of technical support. It attempts to provide a wide array of topics to serve as points of improvement, discussion, or simply topics that you might want to learn. The topics range from good work habits to the way technical support groups establish their own style of work. This book applies theories, models, and concepts synthesized from existing research in other fields - such as management, economics, leadership, and psychology - and connects them to technical support. The goal is to build on the work of others and allow their success to evolve the profession. The book's broad perspective looks at proven practices, legal issues, dealing with customers, utilizing resources, and an array of other topics of interest to tech support professionals."--Page 4 of cover